Competitive adsorption of multicomponent volatile organic compounds on biochar. (November 2021) - Rajabi, Hamid; Hadi Mosleh, Mojgan; Prakoso, Tirto; Ghaemi, Negin; Mandal, Parthasarathi; Lea-Langton, Amanda; Sedighi, Majid
Abstract: Crude oil contaminated lands are recognised to have significant contributions to airborne volatile organic compounds (VOCs) with adverse effects on human health and tropospheric ozone. Soil capping systems for controlling harmful emissions are critical engineering solutions where advanced soil remediation techniques are neither available nor feasible. Studies on the adsorption of single VOC species in biochar have shown promising results as a potential capping material; however, current understanding of mixed gas system and multi-component adsorption of VOCs on biochar which would represent more realistic in situ conditions is very limited. We present, for the first time, the results of a study on competitive adsorption of mixed VOCs, including aromatic and non-aromatic VOCs commonly emitted from crude oil contaminated sites on two types of biochar pyrolysed at 500 °C from wheat straw and bagasse as feedstock. The kinetics of sorption of multicomponent VOCs including acetone, hexane, toluene and p-xylene in biochar are studied based on the results of an extensive experimental investigation using a bespoke laboratory setup. Both biochar types used in this study presented a high sorption capacity for VOC compounds when tested individually (51–110 mg/g). For the multicomponent mixture, the competition for occupying sorption sites on biochar surface resulted in a lower absolute sorption capacity for each species, however, the overall sorption capacity of biochar remained more or less similar to that observed in the single gas experiments (50–109 mg/g). The chemical interactions via hydrogen bonds, electrostatic attraction, and pore-filling were found to be the main mechanisms of adsorption of VOC in the biochar studied. The efficiency of biochar regeneration was assessed through five cycles of adsorption-desorption tests and was found to be between 88% and 96%. The incomplete desorption observed confirm the formation of likely permanent bonds and heel build-ups during the sorption process. Graphical abstract: Image 1 Highlights: Competitive adsorption of aromatic/non-aromatic VOCs on biochar was assessed. The used biochar retained a total adsorption for single and multi-component VOCs. Single uptakes of VOCs from mixed gas reduced due to competitive inhibition. Stacking, hydrogen bonding and electrostatic attraction were adsorption mechanisms.